Correlates and predictors of missed nursing care in hospitals - Bragadóttir, Helga; Kalisch, Beatrice J; Tryggvadóttir, Gudný Bergthora (Journal of clinical nursing, 2017)
Aims and objectives To identify the contribution of hospital, unit, staff characteristics, staffing adequacy and teamwork to missed nursing care in Iceland hospitals. Background A recently identified quality indicator for nursing care and patient safety is missed nursing care defined as any standard, required nursing care omitted or significantly delayed, indicating an error of omission. Former studies point to contributing factors to missed nursing care regarding hospital, unit and staff characteristics, perceptions of staffing adequacy as well as nursing teamwork, displayed in the Missed Nursing Care Model. Design This was a quantitative cross‐sectional survey study. Methods The samples were all registered nurses and practical nurses (n = 864) working on 27 medical, surgical and intensive care inpatient units in eight hospitals throughout Iceland. Response rate was 69·3%. Data were collected in March–April 2012 using the combined MISSCARE Survey‐Icelandic and the Nursing Teamwork Survey‐Icelandic. Descriptive, correlational and regression statistics were used for data analysis. Results Missed nursing care was significantly related to hospital and unit type, participants’ age and role and their perception of adequate staffing and level of teamwork. The multiple regression testing of Model 1 indicated unit type, role, age and staffing adequacy to predict 16% of the variance in missed nursing care. Controlling for unit type, role, age and perceptions of staffing adequacy, the multiple regression testing of Model 2 showed that nursing teamwork predicted an additional 14% of the variance in missed nursing care. Conclusions The results shed light on the correlates and predictors of missed nursing care in hospitals. This study gives direction as to the development of strategies for decreasing missed nursing care, including ensuring appropriate staffing levels and enhanced teamwork. Relevance to clinical practice By identifying contributing factors to missed nursing care, appropriate interventions can be developed and tested.